PENGEMBANGAN MODUL BIOLOGI YANG TERINTEGRASI NILAI-NILAI KEISLAMAN UNTUK MENINGKATKAN PEMAHAMAN DAN KESADARAN PESERTA DIDIK PADA MATERI POKOK KEANEKARAGAMAN HAYATI SMA KELAS X - Utami, Zainab Sinta; Sujarwanta, Agus; Santoso, Handoko (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Development of the Biology Module that integrates Islamic values based on the problems in the Integrated Islamic High School Darul Hikmah Pasir Sakti, East Lampung, the teaching materials used are not in accordance with the school background and learning outcomes in the material of Biodiversity are low. Based on these problems, this study aims to produce a biological module that integrates Islamic values on the subject matter of Biodiversity and effectively increases the understanding and awareness of students in class X. The development of this module uses the Borg and Gall development model. Subjects of assessment are material experts, media experts, linguists, religious experts, education practitioners, and class X students. The instruments used are questionnaires and learning outcomes tests. The results of this study are a Biology module that integrates Islamic values on the subject matter of biodiversity for students of class X. Based on the results of the module quality assessment, the category is very good and effective in increasing students' awareness and understanding. So it can be concluded that the biology module developed is suitable to be used as an independent teaching material for class X students. Keywords: Awareness, Integration Of Islamic Values, Module, Understanding